2021
DOI: 10.1111/jcmm.16671
|View full text |Cite
|
Sign up to set email alerts
|

Extensive serum biomarker analysis in the prethrombotic state of recurrent spontaneous abortion

Abstract: Recurrent spontaneous abortion (RSA) generally refers to the spontaneous loss of two or more pregnancies before 24 weeks of gestational age. 1 About 1%-5% of women of childbearing age experience recurrent miscarriage (spontaneous abortion). 2 The causes of RSA are complex and diverse, usually lacking specific clinical manifestations. The known possible causes of RSA include genetic factors, uterine anomalies, endocrine anomalies, infectious diseases, immune dysfunction, prothrombotic state (PTS), systemic dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
(59 reference statements)
0
6
0
Order By: Relevance
“… 4 , 27 And the thrombotic process involves vascular endothelial cells, coagulation/anticoagulation system, fibrinolytic/antifibrin system, platelets, inflammation, and other factors. 28 Among them, vascular wall damage is caused by endothelial damage of blood vessels. Endothelial cells act as a barrier separating the blood from surrounding tissues and play an indispensable role in the hemostatic system.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 27 And the thrombotic process involves vascular endothelial cells, coagulation/anticoagulation system, fibrinolytic/antifibrin system, platelets, inflammation, and other factors. 28 Among them, vascular wall damage is caused by endothelial damage of blood vessels. Endothelial cells act as a barrier separating the blood from surrounding tissues and play an indispensable role in the hemostatic system.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous observational cohort studies had linked the levels of the biomarkers MIP1b, MCSF, GROa, Eotaxin, MCP3, and SCF in the regulation of embryo implantation ( Gnainsky et al, 2010 ), improve endometrial receptivity ( Gnainsky et al, 2015 ), premature rupture of membranes ( Raba et al, 2021 ), recurrent miscarriage ( Wu et al, 2021 ), reduced developmental potential of an oocyte ( Tan et al, 2017 ), and gestational hypertension ( Lan et al, 2022 ). IP10 has been found to promote the differentiation and migration of T cells toward Th1 and Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] It has also been found that an abnormal coagulation-fibrinolytic system is closely related to spontaneous abortion, often leading to thrombosis of uterine tissue and placenta, resulting in fetal ischemia and eventually abortion. [ 13 15 ] Components of the body natural anticoagulant system, such as Protein S and Protein C, can reflect the body coagulation function. Deficient women have a higher risk of forming blood clots in the placenta, causing placental insufficiency, microthrombi formation in uterine spiral arteries or villus vessels, or even multiple placental infarction, resulting in poor perfusion of utero-placental circulation and an increased risk of fetal death and abortion.…”
Section: Discussionmentioning
confidence: 99%